Effects of a dietary added formaldehyde-propionic acid blend on feed enterobacteria counts and on growing pig performance and fecal formaldehyde excretion - Sbardella,Maicon (2015)
The purpose of this study was to evaluate the effects of a dietary added formaldehyde-propionic acid blend on feed enterobacteria counts and on growing pig performance and fecal formaldehyde excretion. Forty pigs (34.2±1.8kg BW) were used in a randomized complete block design experiment with four treatments, five replications per treatment and two animals per experimental unit (pen). The treatments were: 0.0, 1.0, 2.0, and 3.0g of blend kg-1 of feed. No effects (P>0.05) of dietary added blend levels were observed on average daily gain, average daily feed intake and feed:gain ratio during 1 to 14 and 1 to 28 days of experiment. Increasing dietary levels of blend reduced quadratically (P<0.01) total Enterobacteriaceae counts on 1st and 14th day after feed mixing, allowing to estimate, respectively, 2.63 and 3.35g kg-1 (average 2.99g kg-1) as the formaldehyde-propionic acid blend levels with lowest feed Enterobacteriaceae counts. Therefore, formaldehyde-propionic acid blend can reduce and/or control feed Enterobacteriaceae growth. There was no effect (P>0.05) of blend on fecal formaldehyde excretion on the 28th day of the experimental period. Therefore, the addition of dietary formaldehyde-propionic acid blend up to 3.0g kg-1 of feed reduces the Enterobacteriaceae counts until the 14th day after feed mixing, without any effects on growing pig performance and fecal formaldehyde excretion